THE INFLUENCE OF WORK STUDY CONFLICT, SELF-EFFICACY, AND SOCIAL SUPPORT ON ACADEMIC BURNOUT AMONG WORKING STUDENTS - Muhammad Rayhan Pratama; Imam Yuwono (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study aims to analyze the influence of Work–Study Conflict, self-efficacy, and social support on academic burnout among working students of Universitas Dian Nusantara, cohort 2021. The research employed a quantitative approach with a causal associative research design. The sample consisted of 99 respondents selected using a simple random sampling technique. Data were collected through questionnaires, and multiple linear regression analysis was used as the analytical method. Hypothesis testing was conducted simultaneously using the F-test and partially using the t-test. The results indicate that, partially, Work–Study Conflict has a positive and significant effect on academic burnout, self-efficacy has a negative and significant effect on academic burnout, and social support has a negative and significant effect on academic burnout. Simultaneously, the three independent variables significantly affect academic burnout. These findings confirm that work–study role conflict increases the risk of academic burnout, while self-efficacy and social support function as protective factors that reduce burnout levels.